Synthesis and characterisation of thermally stable Ka[Cu2(p-OC6H4COO)a(CH3(CH2)nCOO)4—a] and [Cu2(p-H3NC6H4COO)a(CH3(CH2)nCOO)4-a]Xa and their reactions with selected ketones / Zaimatul' Azian Kamarazaman - Zaimatul' Azian, Kamarazaman (2012)
This research focussed on the development of the synthetic methods and characterisation (structural, thermal, magnetic and redox properties) of two types of ionic copper(II) mixed-carboxylates: (a) Ka[Cu2(p-OC6H4COO)a(CH3(CH2)nCOO)4-a], and (b) [Cu2(p-H3NC6H4COO)a(CH3(CH2)14COO)4-a]Xa, where a = 1, 2; n = 14, 10, 8, and 6; X = Cl, CH3COO and CF3SO3. These complexes were designed to be thermally stable and magnetic metallomesogens and/or metal-containing ionic liquids. The synthetic methods used to prepare these complexes were one-pot reaction, ligand-exchange reaction, and acid-carbonate-base reaction. A total of twelve (12) complexes were successfully prepared and fully characterised (Table 1). The structural formulas of these complexes were deduced from elemental analyses, FTIR and UV-vis spectroscopies. The thermal properties were determined by TGA and DSC, while the mesomorphic properties were determined by OPM. The magnetic properties were determined by Gouy method using a magnetic susceptibility balance, and the redox properties by cyclic voltammetry. Additionally, GCMS was used to analyze the products formed from the carbon-carbon bond-forming reaction of methyl carbonyl (3,3-dimethyl-2-butanone). The structure of most of the complexes were dimeric paddle-wheel with either square planar or square pyramidal geometry at copper(II) centres. Complex 1 had the highest thermal stability (Tdec = 424oC) compared to the other complexes (Tdec = 200oC – 250oC). Additionally, the complexes with a higher ratio of the alkylcarboxylate ligands (aromatic: aliphatic = 1:3) were more thermally stable; the stability increases with increasing alkyl chain length. However, the opposite trend was noted for the melting temperatures: complexes with a higher ratio of the alkylcarboxylate ligands had a lower melting point. Six of the complexes (Complex 2, Complexes 5 - 9) exhibited metallomesogenic properties. However, the type of mesophase cannot be deduced with certainty from OPM. All complexes were magnetic at room-temperature. Except for Complex 1 which showed a weak ferromagnetic interaction (μeff = 3.12 B.M.; 2J = 60 cm-1), the other complexes had magnetism (μeff = 1.87 B.M. - 2.62 B.M.) which were lower than the spin-only value for two unpaired electrons (μeff = 2.83 B.M.), with variable strength of antiferromagnetic interaction (2J = -78 cm-1 to -346 cm-1). The complexes with a higher ratio of the alkylcarboxylate ligands have a stronger antiferromagnetic interaction. However, the difference in the chain length did not have much effect on the magnetic interaction.